To act or not to act: responses to electronic health record prompts by family medicine clinicians. (13th February 2017) - Zazove, Philip; McKee, Michael; Schleicher, Lauren; Green, Lee; Kileny, Paul; Rapai, Mary; Mulhem, Elie
Abstract : Objective : A major focus of health care today is a strong emphasis on improving the health and quality of care for entire patient populations. One common approach utilizes electronic clinical alerts to prompt clinicians when certain interventions are due for individual patients being seen. However, these alerts have not been consistently effective, particularly for less visible (though important) conditions such as hearing loss (HL) screening. Materials and Methods : We conducted hour-long cognitive task analysis interviews to explore how family medicine clinicians view, perceive, and use electronic clinical alerts, and to utilize this information to design a more effective alert using HL identification and referral as a model diagnosis. Results : Four key direct barriers were identified that impeded alert use: poor standardization and formatting, time pressures in primary care, clinic workflow variations, and mental models of the condition being prompted (in this case, HL). One indirect barrier was identified: electronic health record and institution/government regulations. We identified that clinicians' mental model of the condition being prompted was probably the major barrier, though this was often expressed as time pressure. We discuss solutions to each of the 5 identified barriers, such as addressing physicians' mental models, by focusing on physicians' expertise rather than knowledge to improve their comfort when caring for patients with the conditions being prompted. Conclusions : To unleash the potential of electronic clinical alerts, electronic health record and health care institutions need to address some key barriers. We outline these barriers and propose solutions.